2016
DOI: 10.4049/jimmunol.1501816
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of Functionally Contrasting Signals by Two Mycobacterial PPE Proteins Downstream of TLR2 Receptors

Abstract: As pathogen-associated molecular pattern sensors, the TLRs can detect diverse ligands to elicit either proinflammatory or anti-inflammatory responses, but the mechanism that dictates such contrasting immune responses is not well understood. In this work, we demonstrate that proline–proline–glutamic acid (PPE)17 protein of Mycobacterium tuberculosis induces TLR1/2 heterodimerization to elicit proinflammatory-type response, whereas PPE18-induced homodimerization of TLR2 triggers anti-inflammatory type responses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 64 publications
0
15
0
1
Order By: Relevance
“…Previous investigations revealed that IRAK3 is equally distributed in the cytoplasm and nucleus of human cells and shifts toward the cytoplasm upon immune stimulation (45, 46). We wanted to see, whether this also applies to the ortholog from trout and whether the Irak3 variants might alter this pathogen-stimulated spatial redistribution of the factor.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations revealed that IRAK3 is equally distributed in the cytoplasm and nucleus of human cells and shifts toward the cytoplasm upon immune stimulation (45, 46). We wanted to see, whether this also applies to the ortholog from trout and whether the Irak3 variants might alter this pathogen-stimulated spatial redistribution of the factor.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that though the N-terminal regions of PPE proteins share a conserved sequence, they may be structurally different. Earlier we demonstrated that N-terminal fragments of PPE17 and PPE18 proteins induce contrasting signaling cascades in macrophages due to their different conformations [30,35,42,43]. Thus, it is interesting to speculate that though the N-terminal region of about 180 amino acid residues of PPE proteins are conserved, the subtle variation in the sequence and length in the C-terminal region could change the three-dimensional epitopes of PPE proteins resulting in more unique immunoreactivity to N-PPE17.…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis и компоненты ее клеточной стенки распознаются TLR1, TLR2, TLR4, TLR7 и TLR9 [45,49,79,103], что приводит к MyD88-зависимой активации антибактериальных эффекторных путей и продукции NO-оксидазы, а также провоспалительных цитокинов, таких как TNFα, IL-12, хемокинов [73]. Такие гликолипиды M. tuberculosis, как липо арабиноманнан, липоманнан и фосфатидилинозитол маннозид, а также белок пролин-пролин-глутаминовой кислоты (PPE)-17 подают сигнал через гетеродимеры TLR2-TLR1 [41,105]. При этом показано, что миколовые кислоты могут ингибировать TLR2 в альвеолоцитах 1 и 2 типа и альвеолярных макрофагах [93].…”
Section: Toll-like рецепторыunclassified